Elective versus deferred stenting following subintimal recanalization of coronary chronic total occlusions. Issue 3 (10th May 2014) - Visconti, Gabriella; Focaccio, Amelia; Donahue, Michael; Briguori, Carlo
<x xml:space="preserve">Abstract</x> Subintimal tracking and re‐entry (STAR) technique has been described as a bailout strategy for coronary total occlusion (CTO) recanalization. However, the length of the dissected segment represents a major concern. The aim of this study is, to evaluate whether "deferred" stent implantation may limit the total stent length following STAR recanalization of CTO. All consecutive patients with CTO in a native coronary artery treated by successful STAR technique in our institution were included. In the first period (March 2004–December 2009) all procedures were completed with stent implantation (Elective Stent Group; n = 60). Thereafter (January 2010–June 2012) stent implantation was postponed until a scheduled (within 3 months) angiographic follow‐up (Deferred Stent Group; n = 69). The dissection length was 75 ± 37 mm in the Elective Stent Group and 83 ± 31 mm in the Deferred Stent Group (P = 0.22). In the Deferred Stent Group, at the angiographic follow‐up, the dissection length was significantly shorter than at the index procedure (40 ± 35 mm versus 83 ± 31 mm, P <0.001). The total stent length was significantly shorter in the Deferred Stent Group versus the Elective Stent Group (22 ± 33 mm versus 56 ± 28 mm; P < 0.001). At six‐month follow‐up, rate of cardiac death and myocardial infarction (6.7% vs 0; P = 0.049) and of stent thrombosis (5% vs 0%; P = 0.10) were higher in the Elective Stent Group. The present study suggests that deferring stenting implantation following STAR recanalization (1) limits the stent length and (2) is associated with a lower rate of objective endpoints. © 2014 Wiley Periodicals, Inc.